Achieving orphan designation for placental insufficiency: annual incidence estimations in Europe. (6th February 2019) - Spencer, R; Rossi, C; Lees, M; Peebles, D; Brocklehurst, P; Martin, J; Hansson, SR; Hecher, K; Marsal, K; Figueras, F; Gratacos, E; David, AL; et al.
Abstract : Objective: To determine whether a novel therapy for placental insufficiency could achieve orphan drug status by estimating the annual incidence of placental insufficiency, defined as an estimated fetal weight below the 10th centile in the presence of abnormal umbilical artery Doppler velocimetry, per 10 000 European Union (EU) population as part of an application for European Medicines Agency (EMA) orphan designation. Design: Incidence estimation based on literature review and published national and EU statistics. Setting and population: European Union. Methods: Data were drawn from published literature, including national and international guidelines, international consensus statements, cohort studies and randomised controlled trials, and published national and EU statistics, including birth rates and stillbirth rates. Rare disease databases were also searched. Results: The proportion of affected pregnancies was estimated as 3.17% (95% CI 2.93–3.43%), using a weighted average of the results from two cohort studies. Using birth rates from 2012 and adjusting for a pregnancy loss rate of 1/100 gave an estimated annual incidence of 3.33 per 10 000 EU population (95% CI 3.07–3.60 per 10 000 EU population). This fell below the EMA threshold of 5 per 10 000 EU population. Conclusions: Maternal vascular endothelial growth factor gene therapy for placental insufficiency was granted EMA orphan status in 2015 after we demonstrated that it is a rare, life‐threatening or chronically debilitating and currently untreatable disease. Developers of other potential obstetric therapies should consider applying for orphan designation, which provides financial and regulatory benefits. Tweetable abstract: Placental insufficiency meets the European Medicines Agency requirements for orphan disease designation. Tweetable abstract: Placental insufficiency meets the European Medicines Agency requirements for orphan disease designation.